Pandangan Yuridis Sosiologis Fenomena Street Justice Di Dalam Kehidupan Bermasyarakat - Fuadi Isnawan (Universitas Ahmad Dahlan, 2018)
The law in people's lives serves as a safeguard in living life. The law is present as a guardian of society. However, in fact, the law often found unimplemented. This fact will effect on providing security for the community. The Powerless of the law would lead to what so called street justice or court justice. The long way to get legal procedure grows the society’s anger and leads them to take down the punishment by them self. The phenomenon of street justice influenced by several factors, such as the lack of law awareness and its legal compliance. In this paper, we will use empirical research with the perspective of legal sociology.